Clinical diagnostics of fibrillinopathies (type 1) - E. L. Trisvetova (Российский кардиологический журнал)
Diagnostic criteria are presented for the syndromes related to mutations of fibrillin gene type 1 (such as Marfan syndrome, ectopia lentis, MASS phenotype, mitral valve prolapse syndrome, stiff skin syndrome, Shprintzen-Goldberg syndrome) and for the acromelic group of dysplasias (such as geleophysic dysplasia, Weill-Marchesani syndrome, and acromicria).